2009
DOI: 10.1039/b812325j
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective access to 3I-O-substituted-β-cyclodextrin derivatives

Abstract: Formation of a copper(ii)-beta-cyclodextrin (beta-CD) complex in an aqueous medium allowed the regioselective introduction into the oligosaccharide of a benzyl or a bromo-allyl substituent at O-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Differences in the steric accessibility and acidity of the three types of hydroxyls in the molecule have been taken into account to conceive efficient position-selective and face-selective chemical functionalization methodologies. [17][18][19][20][21][22][23][24][25][26][27] A variety of multivalent conjugates with diverse architectures becomes then accessible through appropriate ligation chemistries (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the steric accessibility and acidity of the three types of hydroxyls in the molecule have been taken into account to conceive efficient position-selective and face-selective chemical functionalization methodologies. [17][18][19][20][21][22][23][24][25][26][27] A variety of multivalent conjugates with diverse architectures becomes then accessible through appropriate ligation chemistries (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…As evaluated in the HTS fluorescent assay summarised in Figure 5, most of the tested nucleophiles exhibit a weak phosphonothioate activity. Thus, as shown by the colour-coded pattern ( Figure 5), HOBt (65), peracids 68 and 69, iodosobenzoic acid (IBA, 71), which according to the literature survey and to our previous experiments give satisfactory results with Gtype agents and the HTS assay using fluorogenic probes bearing the coumarin unit directly linked to the phosphorus, [13] in our case provided very disappointing results (which were further confirmed for the hydrolysis of PhX (3 b)). As we expected, the quaternised pyridinealdoximes, which are described as being the best OP-poisoned AChE reactivators, display the highest phosphonothioate activity, 2-PAM (11) being slightly better.…”
Section: Resultsmentioning
confidence: 94%
“…Our library contained oximes (such as pralidoxime (2-PAM, 11) and its derivatives (12)(13)(14)(15)(16)(17)(18)(19), trimedoxime (TMB-4, 20), obidoxime (21) and HI-6 (22)) already known for their ability to reactivate OPNA-inhibited AChE. Their efficiencies were compared with those of other oximes and strong nucleophiles such as hydroxy-or mercaptopyridines, hydroxypyridinones, hydroxylamines, pyrimidines, hydroxamic acids, quinazolines and peracids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jind rich and Tislerova later reported 24 a direct synthesis of mono-3-O-cinnamylated b-CD (29% yield) in aqueous sodium hydroxide along with the formation of a large amount of polysubstituted by-products. More recently, Masurier et al reported 25 a novel method to regioselectively modify one of the O3-positions of native b-CD based on the formation of a temporary copper(II)-b-CD complex; the methodology appears to be only suitable for bulky electrophiles such as benzylic and 3-brominated allyl groups to afford the O3-monoalkylated b-CDs in 38e42% yields, together with some O2-substituted by-products. Remarkably, a de-O-benzylation method by using iodineetriethylsilane (I 2 eEt 3 SiH) as the reagent has been reported to regioselectively deprotected all O3-benzyl groups from per-2,3,6-benzylated a-CD.…”
Section: Introductionmentioning
confidence: 98%